2016
DOI: 10.1021/acs.jmedchem.5b01333
|View full text |Cite
|
Sign up to set email alerts
|

New 4-Functionalized Glutamate Analogues Are Selective Agonists at Metabotropic Glutamate Receptor Subtype 2 or Selective Agonists at Metabotropic Glutamate Receptor Group III

Abstract: The metabotropic glutamate (Glu) receptors (mGluRs) play key roles in modulating excitatory neurotransmission in the brain. In all, eight subtypes have been identified and divided into three groups, group I (mGlu1,5), group II (mGlu2,3), and group III (mGlu4,6-8). In this article, we present a L-2,4-syn-substituted Glu analogue, 1d, which displays selective agonist activity at mGlu2 over the remaining mGluR subtypes. A modeling study and redesign of the core scaffold led to the stereoselective synthesis of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…In contrast to LimGluR3, which shows very robust photoactivation with D-MAG-0 (∼70%), we show in this study that SNAP-mGluR3 is weakly agonized by BGAG (∼20%). This is consistent with pharmacological studies that have shown that many 4-functionalized glutamate compounds have a higher affinity for mGluR2 than mGluR3 (32). In addition, SNAP-mGluR3 has a more pronounced dependence on BGAG length than SNAP-mGluR2.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to LimGluR3, which shows very robust photoactivation with D-MAG-0 (∼70%), we show in this study that SNAP-mGluR3 is weakly agonized by BGAG (∼20%). This is consistent with pharmacological studies that have shown that many 4-functionalized glutamate compounds have a higher affinity for mGluR2 than mGluR3 (32). In addition, SNAP-mGluR3 has a more pronounced dependence on BGAG length than SNAP-mGluR2.…”
Section: Discussionsupporting
confidence: 90%
“…The formation of compounds 9 is likely to proceed via Mannich‐type reaction of enolized pyrazolidin‐3‐one 7 . Notably, carboxylic acid derivatives, both cyclic and acyclic, usually require usage of either strong bases, or Lewis acid/base combination, to undergo the reaction with iminium ion. To the best of our knowledge, no such reactions in the presence of Bronsted acid were reported until now.…”
Section: Resultsmentioning
confidence: 99%
“…The symptomatic and neuroprotective properties of group III mGluRs agonists are prevented in mGluR 4 knockout mice, which suggest that the modulation of mGluR 4 has the potential to exert antiparkinsonian activity in animal models. Overall, the pharmacological activation with mGluR 2 /mGluR 3 [175][176][177][178][179][180] and mGluR 4 [181][182][183][184][185][186] with agonists and positive allosteric modulators may offer an alternative approach for PD therapeutics.…”
Section: Metabotropic Glutamate Receptorsmentioning
confidence: 99%